2005
DOI: 10.1002/arch.20063
|View full text |Cite
|
Sign up to set email alerts
|

A transporter for phenolamine uptake in the arthropod CNS

Abstract: Biogenic monoamines play central roles in the nervous control of physiological processes in both vertebrates and invertebrates, each using a suite of neurotransmitters tailored through evolution. Among the ancillary proteins necessary for the deployment of monoamine transmitters are membrane-bound transporters that enable the reuptake of synaptically released transmitters. Transporters responsible for monoamine uptake include a novel transporter discovered in a pest insect, the cabbage looper Trichoplusia ni, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…39 Octopamine has a similar structure to dopamine, and it has been suggested that the dopamine transporter could transport octopamine. 40 However, tests of Drosophila dopamine transporter (dDAT) expressed in MDCK cells found that octopamine was not a good substrate for dDAT.…”
Section: Resultsmentioning
confidence: 99%
“…39 Octopamine has a similar structure to dopamine, and it has been suggested that the dopamine transporter could transport octopamine. 40 However, tests of Drosophila dopamine transporter (dDAT) expressed in MDCK cells found that octopamine was not a good substrate for dDAT.…”
Section: Resultsmentioning
confidence: 99%
“…Trace Amines and Their Receptors 571 (Roeder and Gewecke, 1989;McClung and Hirsh, 1998;Gallant et al, 2003;Donly and Caveney, 2005), with some evidence for species specificity in the transporters present (Roeder, 2005).…”
Section: B Storage and Releasementioning
confidence: 99%
“…However, a plasma membrane OA transporter has not been identified in the fly. Surprisingly, a high affinity OA transporter has been identified in the cabbage looper Trichoplusia ni ( T. ni ) and several other insect species (Donly et al, 2007; Malutan et al, 2002), but is absent in Drosophila and other Diptera n species as well as bees ( Hymenoptera ) (Donly and Caveney, 2005). T. ni also express a high affinity DA transporter (Gallant et al, 2003).…”
Section: Octopamine Uptake and Metabolism In Flies Vs Other Insectsmentioning
confidence: 99%